The philosophy of miracles - Corner, David (Senior lecturer) (Continuum studies in philosophy., 2007)
Philosophers who wish to argue for the rationality of belief in God frequently employ a 'god-of-the-gaps' strategy. This strategy consists in trying to find a phenomenon that cannot be explained by natural science, and insisting that it can be explained only by reference to the activity of God. Philosophical discussion of miracles usually revolves around the attempt to link a miracle to God in just this way. One of the problems with this approach is that it is very difficult to identify anything as being forever beyond the power of science to explain. Science continues to advance upon the terr.